2003
DOI: 10.1051/lait:2003034
|View full text |Cite
|
Sign up to set email alerts
|

Article

Abstract: -The proteolytic system of lactic acid bacteria has been characterised in detail and numerous modified strains with null or increased specific proteolytic activities have been constructed or identified among natural strains. Based on this knowledge, our objective was to ferment milk with modified strains and produce mixtures of peptides with specific features corresponding to potential bio-activities. We used a collection of Lactococcus lactis negative mutants for peptidase activities available in the laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The j-CN-derived sequence VIESPPEIN was produced by all the analyzed L. helveticus strains. This peptide was previously detected in milk fermented by a Lactococcus lactis wild-type strain (Algaron et al 2004). Similarly, Robert et al (2001) obtained the VIESPPEIN peptide using L. helveticus NCC 619 and confirmed the ACE inhibitory activity of this sequence.…”
Section: Studies On the Biological Activities Of Obtained Peptide Seqsupporting
confidence: 54%
“…The j-CN-derived sequence VIESPPEIN was produced by all the analyzed L. helveticus strains. This peptide was previously detected in milk fermented by a Lactococcus lactis wild-type strain (Algaron et al 2004). Similarly, Robert et al (2001) obtained the VIESPPEIN peptide using L. helveticus NCC 619 and confirmed the ACE inhibitory activity of this sequence.…”
Section: Studies On the Biological Activities Of Obtained Peptide Seqsupporting
confidence: 54%
“…Proline at the second position of a nonameric peptide also resulted in a dramatic drop of the OppA binding affinity (122). Phosphorylated peptides and peptides high in proline content are more resistant to hydrolysis by proteolytic enzymes (123, 124). Oligopeptides containing VPP and IPP sequences could release branched chain amino acids (BCAAs) in the presence of specific peptidases.…”
Section: Discussionmentioning
confidence: 99%
“…lactis, L. lactis ssp. Cremoris and Enterococcus faecalis (Algaron et al, 2004;Ashar and Chand, 2003;Fuglsang et al, 2003b;Gobbetti et al, 2000;Herna´ndez-Ledesma et al, 2004;Leclerc et al, 2002;Muguerza et al, 2006;Nakamura et al, 1995;Quiro´ s et al, 2007;Robert et al, 2004;Rodríguez-Figueroa et al, 2010;Rokka et al, 1997;Shuangquan and Taku, 2008;Vermeirssen et al, 2003;Yamamoto et al, 1994aYamamoto et al, , b, 1999. In our previous study, 28 probiotic Lactobacillus strains were used to ferment goat milk to screen for production ACE-inhibitory peptides, the results showed that 20 strains had ACE inhibitory activity and among them of 4 strains including Lactobacillus reuteri, Lactobacillus bulgaricus, Lactobacillus rhamnosus and Lactobacillus helveticus were especially significant as producers of ACE-inhibitory peptides (He et al, 2012).…”
Section: Introductionmentioning
confidence: 99%